1956
DOI: 10.1136/oem.13.3.166
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Ventilatory Capacity and Simple Pneumoconiosis in Coalworkers: The Effect of Population Selection

Abstract: The diagnosis in life of coalworkers' pneumoconiosis is based on the industrial history and the chest radiograph. The most striking complaint is excessive breathlessness on exertion. The relationship of this symptom to radiological abnormality is of practical importance in assessing compensation; in most schemes the assumption is made that if a readily diagnosable degree of pneumoconiosis is present and the man is breathless, then the breathlessness is caused by the pneumoconiosis if no other cause is apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
0

Year Published

1959
1959
1970
1970

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 21 publications
(20 reference statements)
7
25
0
Order By: Relevance
“…6) that the proportion of men with respiratory symptoms in any given age-group increases as the x-ray category rises, is consistent with the findings of Hart and Aslett (1942), Zorn (1949), Worth and Dickmans (1950), and Beckmann (1951). On the other hand, Bohme and Lent (1951), Hugh-Jones (1955), andHiggins et al (1956) have reported a higher prevalence of symptoms in miners without pneumoconiosis than in those with this condition, whereas Newell and Browne (1955) and Pemberton (1956) have been unable to show any relationship. It is worth noting that a large number of men even with advanced categories of pneumoconiosis have no respiratory symptoms.…”
Section: Pneumoconiosis and Respiratory Symptomsmentioning
confidence: 98%
See 1 more Smart Citation
“…6) that the proportion of men with respiratory symptoms in any given age-group increases as the x-ray category rises, is consistent with the findings of Hart and Aslett (1942), Zorn (1949), Worth and Dickmans (1950), and Beckmann (1951). On the other hand, Bohme and Lent (1951), Hugh-Jones (1955), andHiggins et al (1956) have reported a higher prevalence of symptoms in miners without pneumoconiosis than in those with this condition, whereas Newell and Browne (1955) and Pemberton (1956) have been unable to show any relationship. It is worth noting that a large number of men even with advanced categories of pneumoconiosis have no respiratory symptoms.…”
Section: Pneumoconiosis and Respiratory Symptomsmentioning
confidence: 98%
“…Soon afterwards, however, evidence began to accumulate which threw doubt on the commonly held belief that simple pneumoconiosis was a disease causing substantial disability (Lavenne and Belayew, 1953;Gilson and Hugh-Jones, 1955;Carpenter et al, 1956).…”
Section: Pneumoconiosismentioning
confidence: 99%
“…FEV, or FEV 0.75 sec [21] less the initial 100 ml according to C ar pe n t e r [5]. Peak flow [19,43,44], for instance using a peak flow meter [11,12,25,43].…”
Section: Selection Of a Measurement Criterionmentioning
confidence: 99%
“…The validation of this test as an objective measure of respiratory disability and the reasons for preferring it to the M.B.C. measured directly have been considered previously (Carpenter et al, 1956). Its accuracy, simplicity, and repeatability are characteristics admirably suited to field investigations, particularly when these are continued over a number of years.…”
mentioning
confidence: 99%